Acute pancreatitis in COVID-19 patients: true risk?. (4th May 2021) - Bulthuis, Margo C.; Boxhoorn, Lotte; Beudel, Martijn; Elbers, Paul W. G.; Kop, Marnix P. M.; van Wanrooij, Roy L. J.; Besselink, Marc G.; Voermans, Rogier P.
Abstract: Background: A relation between coronavirus disease 2019 (COVID-19) and acute pancreatitis has been suggested. However, the incidence and clinical relevance of this relation remain unclear. Objective: We aimed to investigate the incidence, severity and clinical impact of acute pancreatitis in patients with COVID-19. Methods: This is a cross-sectional study of a prospective, observational cohort concerning all COVID-19 patients admitted to two Dutch university hospitals between 4 March 2020 and 26 May 2020. Primary outcome was acute pancreatitis potentially related to COVD-19 infection. Acute pancreatitis was defined according to the revised Atlanta Classification. Potential relation with COVID-19 was defined as the absence of a clear aetiology of acute pancreatitis. Results: Among 433 patients with COVID-19, five (1.2%) had potentially related acute pancreatitis according to the revised Atlanta Classification. These five patients suffered from severe COVID-19 infection; all had (multiple) organ failure and 60% died. None of the patients developed necrotizing pancreatitis. Moreover, development of acute pancreatitis did not lead to major treatment consequences. Conclusions: In contrast with previous research, our study demonstrated that COVID-19 related acute pancreatitis is rare and of little clinical impact. It is therefore debatable if acute pancreatitis in COVID-19 patients requires specific screening. We hypothesize that acute pancreatitis occurs in patients with severe illness due to COVID-19 infection as a result of transient hypoperfusion and pancreatic ischemia, not as a direct result of the virus.